A SIMPLE METHOD OF DNA EXTRACTION OF MYCOBACTERIUM TUBERCULOSIS FROM SPUTUM CULTURES FOR SEQUENCING ANALYSIS - Koentjoro, Maharani Pertiwi; Donastin, Adyan; Prasetyo, Endry Nugroho (African Journal of Infectious Diseases (AJID), 2021)
Background: Concern has been raised about DNA extraction from Mycobacterium tuberculosis due to its complex procedure. This study demonstrates a simple and fast DNA extraction method of mycobacterial genome to subsequent molecular investigation, such as Polymerization Chain Reaction (PCR) amplification, with species-specific primers and sequencing. Materials and Methods: Total DNA was isolated from M. tuberculosis cultured by using boil method. DNA was evaluated via measures of DNA quantity and quality (absorbance at 230, 260 and 280 nm), DNA integrity (electrophoresis). Molecular tests were tested namely PCR and sequencing. Conclusions: The quality of DNA obtained is acceptable for PCR and sequencing analysis. These findings demonstrate that the method used is inexpensive and suitable for minimum infrastructure facilities.